Regulation of E-box DNA binding during in vivo and in vitro activation of rat and human hepatic stellate cells. Issue 5 (1st November 2001) - Vincent, K J; Jones, E; Arthur, M J P; Smart, D E; Trim, J; Wright, M C; Mann, D A
Abstract : BACKGROUND: Activation of hepatic stellate cells (HSCs) to a myofibroblastic phenotype is a key event in liver fibrosis. Identification of transcription factors with activities that are modulated during HSC activation will improve our understanding of the molecular events controlling HSC activation. AIMS: To determine if changes in E-box DNA binding activity occur during in vitro and in vivo activation of rat and human HSCs and to investigate mechanisms underlying any observed changes. METHODS: Nuclear extracts were prepared from rat HSCs isolated and cultured from normal and carbon tetrachloride injured rat livers and from HSCs isolated from human liver. EMSA analysis of E-box DNA binding activity was performed on nuclear extracts to determine changes during HSC activation. Western and northern blot analysis of MyoD and Id1 basic helix-loop-helix (bHLH) proteins was performed to confirm expression in HSC. RESULTS: HSC activation was associated with inducible expression of two low mobility E-box binding complexes that were immunoreactive with an anti-MyoD antibody. MyoD mRNA expression was found at similar levels in freshly isolated and activated HSCs; in contrast, MyoD protein expression was elevated in activated HSCs. Activation of rat HSCs was accompanied by reduced expression of the inhibitory bHLH protein Id1. CONCLUSIONS: In vitro and in vivo activation of rat and human HSCs is accompanied by induction of MyoD binding to E-box DNA sequences which appears to be mechanistically associated with elevated MyoD protein expression and reduced expression of the inhibitory Id1 protein. Clarification of the role of MyoD and Id1 proteins in HSC activation and liver fibrogenesis is now required.